Covid-19 and international business : change of era - Marinov, Marin, 1948-; Marinova, Svetla Trifonova (New York, NY : Routledge, 2021)
"The Covid-19 pandemic has induced a crisis grasping the world abruptly, simultaneously, and swiftly. As a critical juncture, it ignited a change of era for international business. This book illustrates how governments have dealt with the pandemic and the consequent impacts on international business. It also explores the disrupted operations and responses of businesses as their worldwide interconnectivity has been seriously threatened. The book discourses multidirectional aspects of the effects of Covid-19 on international business, ranging from the juxtaposing forces disrupting globalization and installing a change of era through decoupling of technological, production and knowledge flows to its stimulating aspects to the strategic response on business, industry and state level. The book contains thirty chapters that offer a multidimensional interpretation of impacts of Covid-19 on international business theory and practice. Employing the latest state of knowledge on the topic, the book is aimed at international business audience - scholars, students and managers who need to understand better the nature, scope and scale of the impacts of the pandemic on international business"--
The Impact of COVID-19 on the World Economyand the EU -- Impact on the World Economy -- The EU Economy -- The Legacy of COVID-19 Pandemic -- The End of the Beginning -- Permanent Legacy of the Pandemic -- Order Out of Chaos -- References -- Part II: COVID-19: Industry Perspectives and Business Models -- 8. COVID-19 and the Changing Perception of Strategic Industries: Implications for International Business -- Introduction -- Strategic Industries and Crises: An Overview -- COVID-19, Strategic Industries and International Business Dynamics
OCLC-licensed vendor bibliographic record.
Keywords: International trade; International business enterprises -- Management; COVID-19 (Disease) -- Economic aspects; BUSINESS & ECONOMICS / International / General; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Strategic Planning